The Risk of Corruption and Money Laundering: An Analysis of Personal Predespositions and Socio-Economic Challenges - Andrey Hasiholan Pulungan; Hardhana Setiawan; Faris Windiarti (SocioEconomic Challenges)
Corruption and money laundering have been persistent issues in Indonesia and beyond, causing significant economic damage to organizations and countries. This study, thus, aims to examine the impact of gender, age, and workplace on the fraudulent activities of perpetrators involved in corruption and money laundering fraud in Indonesia. The study analyzed 310 cases from the Decision Directory of the Supreme Court of the Republic of Indonesia involving individuals engaged in fraudulent activities. Using logistic regression (LR), the research found that age and workplace are associated positively to the likelihood of ones to commit to fraud. Elder fraudsters are documented to have 1,72 higher possibility to commit to fraud compared to younger fraudsters. Similarly, ones working in public sector are documented to have 2,26 higher possibility to commit to fraud compared to private sector. When interacting the age and workplace, it is found that in private sector, the possibility of ones committed to fraud increases when their age is higher. This research provides valuable insights for academia and practitioners by examining real corruption and money laundering cases in Indonesia to understand the factors that may influence the decision-making process of individuals involved in fraudulent activities. The study concludes that considering factors such as age and workplace could improve the effectiveness of criminal profiles in practical applications. It is essential to identify and prevent these widespread offenses by using such profiles.